Evaluation of the content of tannins, crude protein and weight of a thousand grains of different grain sorghum hybrids (Semiárida, 2020)
The aim of this report is to show data about the content of equivalent of tannic acid, raw protein, weight of one thousand grains and possible co-relations in 54 hybrids of grainy sorghum cultivated in the semiarid "pampeana" region. The results obtained on material sowed during the 80/81 period in the Experimental Field of the "Facultad de Agronomía" of de UNLPam. are presented here. A highly meaningful co-relation, between the weight of one thousand grains and the equivalent percentage in tannic acid detected; no co-relation between the tannic nature and the raw protein was obtained.